Calling Customer Role of Intent Repeat Order Partners Home Food Kita Perm BULOG Southeast Sulawesi Regional Office - Anggraeni Damayanti Salam; Haedar Akib; Aris Baharuddin (Jurnal Office, 2020)
This study aims to determine the role of calling customer on the intention to repeat order of our food house partners perm BULOG Southeast Sulawesi Regional Office. This study uses a quantitative approach, a descriptive research type, with a research population of 304 partners and a sample of 75 partners. Data collection techniques used are through observation, questionnaires (questionnaires), and documentation. The data that has been obtained from the research results are processed using data analysis and using the SPSS.20 software application which consists of descriptive analysis techniques and inferential statistical analysis. The research results show that the role of calling customers for our food house partners perm BULOG Southeast Sulawesi Regional Office is in the category satisfactory with a percentage level of 61.4 percent, and for the intention of repeating orders for our home food partners perm BULOG Southeast Sulawesi Regional Office is in the high category with a percentage of 57.7 percent based on these data, the level of relationship is in the very strong category. It can be concluded that there is a positive and significant effect on the role of calling customer on the intention to repeat orders for our food house partners, perm BULOG, Southeast Sulawesi Regional Office.